AN APPLICATION OF DOCTRINE OF NECESSITY: PREVIOUS CONSTITUENT ASSEMBLY OF NEPAL AND ITS TIME EXTENSION TO AVOID CONSTITUTIONAL UNCERTAINTY - Vijay Pd. Jayshwal (Fakultas Hukum Universitas Gadjah Mada, 2015)
This paper aims to investigate issues in relation of constitutional doctrine which had potential debate among the jurists of Nepal for the issues of time extension. The paper will also argue some weaknesses in the constituent assembly and their role expected by the people of Nepal. This paper will discuss about the evolution of constitution in Nepal, its features, the principle of Constitutionalism embodied in Nepalese constitution. This paper will further argue about the legitimacy of Doctrine of Necessity and its application in Nepal. In last, this paper will show the possibility of constitutional uncertainty by newly elected constituent assembly. Penulisan ini dalam rangka mengkaji doktrin konstitusional yang tengah ramai diperdebatkan oleh para ahli hukum di Nepal, khususnya berkaitan dengan isu mengenai perpanjangan waktu. Melalui tulisan ini, terdapat temuan yang menunjukkan beberapa kelemahan yang ada dalam majelis konstituate Nepal di samping peran-perannya sebagaimana yang diharapkan oleh rakyat Nepal. Tulisan ini membahas pula mengenai evolusi konstitusi Nepal sebagaimana diwujudkan dalam prinsip-prinsip konstitusionalism yang dianut oleh Konstitusi Nepal. Lebih lanjut, berkaitan dengan legitimasi dari Doctrin of Necessity dan penerapannya di Nepal. Pada akhirnya, tulisan ini akan memberikan gambaran mengenai kemungkinan ketidakpastian secara konstitusional berkaitan dengan kondisi majelis konstituante yang baru saja terpilih.